2014
DOI: 10.1039/c4cc01956c
|View full text |Cite
|
Sign up to set email alerts
|

Water soluble octa-functionalized POSS: all-click chemistry synthesis and efficient host–guest encapsulation

Abstract: A series of water soluble octa-functionalized POSSs were facilely synthesized via thiol-ene and Menschutkin click chemistry. Among them, octa-alkynyl POSS further reacted with azide-terminal alkyl long chains, resulting in a well-defined, amphiphilic octopus-like POSS. For the first time it was used for host-guest encapsulation and it exhibited an ultrahigh loading capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 27 publications
(2 reference statements)
1
55
0
Order By: Relevance
“…The final refined structure ( Figure 2) reveals unambiguously that this compound is cubic T 8 . This evidence strongly supports our previous characterizations by NMR ( 1 H, 13 C, and 29 Si) spectroscopy and mass spectrometry. Its crystalline data and structure refinement parameters are given in Tables S1-S3.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The final refined structure ( Figure 2) reveals unambiguously that this compound is cubic T 8 . This evidence strongly supports our previous characterizations by NMR ( 1 H, 13 C, and 29 Si) spectroscopy and mass spectrometry. Its crystalline data and structure refinement parameters are given in Tables S1-S3.…”
Section: Resultssupporting
confidence: 91%
“…[10] Functionalized SQs play important roles in the preparation of hybrid nanocomposites. [11][12][13] As organic-inorganic hybrid molecules, SQs have good thermal stability, high water-resistance, and high corrosion-resistance and are also good electrical insulators. Acrylate- [14,15] and epoxy-functionalized [16,17] SQs were used to prepare some organic-inorganic hybrid photopatternable materials.…”
Section: Introductionmentioning
confidence: 99%
“…The three-dimensional structure of the silicon-oxygen (Si-O) core is inevitably responsible for high thermal stability and stiffness, whereas the terminal organic reactive functional groups can be enabled to make the covalent bond between POSSs and polymers, which results in the solid progress of organic-inorganic hybrid materials [9,10]. POSS properties have been tuned [11][12][13][14][15] by incorporating various end-group moieties (functionalities), such as acrylates, Polymers 2017, 9, 192 2 of 8 methacrylate, alcohols, amines, carboxylic acids, epoxides, fluoroalkyls, halides, and imides, through self-polymerization reactions, which include self-condensing vinyl polymerization, poly-condensation reactions, ring-opening polymerization, and "ene-click" reactions [16][17][18]. Methacrylate-functionalized POSSs provide improved thermal stability and flame retardancy.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, as our recent research findings, reported that after being conjugated, the toxicity and gene-transfer efficiency of nanoparticles have been improved, while attempting to modify the surface of hPAMAM and PAMAM dendrimers by using phenylalanine, glutamic acid and arginine. In this study, the improved genetransfer efficiency was attributed to the synergistic effect of the proton sponge, resulting from the induction of the interpolymer secondary amines as well as hydrophobic interactions between hydrophobic groups of amino acids present on the surface of the dendrimers (Tang et al, 1996;Han et al, 2014). Wang et al (2010) showed that the phenylalanine-modified hPAMAM polymer leads to a decrease and increase in the toxicity and gene-transfer efficiency, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic cationic polymers as non-viral gene delivery carriers, compared to viral gene delivery carriers, have demonstrated a higher safety profile without undesirable immune responses and malicious transformation, proving to be a favorable candidate for clinical gene therapy (Takakura et al, 2002;Pack et al, 2005;Park et al, 2006;Han et al, 2014). On the other hand, the currently-available cationic polymers have not yet been shown to be a suitable vector for clinical application.…”
Section: Introductionmentioning
confidence: 99%